My Life in the Purple Kingdom - BrownMark (Musician); Uhrich, Cynthia M. (Book collections on Project MUSE., 2020)
"Prince's bassist BrownMark on growing up in Minneapolis, joining Prince and The Revolution, and his life in the purple kingdom"--